2013
DOI: 10.1590/s2317-17822014000100003
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and auditory processing abilities: performance of adults in dichotic listening tests

Abstract: Purpose: To evaluate and compare the dichotic listening abilities in non-hearing-impaired adults monolingual speakers of the Brazilian Portuguese language (CG) and simultaneous Brazilian Portuguese-German (GG) bilingual speakers or successive Brazilian Portuguese-Italian bilingual speakers (IG). Methods: This is about an observational, descriptive, transverse and quantitative research. The sample consisted of 87 subjects aged between 18 and 55 years, divided into: Control Group (CG), of 30 monolingual speake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
(31 reference statements)
0
13
1
Order By: Relevance
“…The Brazilian Portuguese Sentence List Test (SLP-BR) has been widely used in research and in clinical practice, with different assessment goals and in diverse populatio ns (14,15,16,17,18,19,20,21,22,23,24) . Thus, the objective of developing a dichotic version of SLP-BR was to create a material that enabled research on the ability of figure-ground discrimination for verbal stimuli, through the task of binaural integration and separation, using sentences that represent conditions of everyday communication (24) .…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian Portuguese Sentence List Test (SLP-BR) has been widely used in research and in clinical practice, with different assessment goals and in diverse populatio ns (14,15,16,17,18,19,20,21,22,23,24) . Thus, the objective of developing a dichotic version of SLP-BR was to create a material that enabled research on the ability of figure-ground discrimination for verbal stimuli, through the task of binaural integration and separation, using sentences that represent conditions of everyday communication (24) .…”
Section: Discussionmentioning
confidence: 99%
“…However, from the perspective of the auditory system and the influence on auditory skills, the number of studies is still small. Previous studies have shown that exposure to two different languages can benefit the development of a person's auditory system (6)(7)(8)(9)(10)(11)12) . This is because such person faces situations in which his or her mother tongue promotes a linguistic context that makes information processing faster and more effective (12,13) .…”
Section: Introductionmentioning
confidence: 99%
“…These studies evaluated the inputs and outputs of languages such as English, Portuguese, German, Italian and Japanese (4,5) . All had a common oral language used as a point of reference.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of research focused on translation and bilingualism is surprising, and as new social paradigms arise, the necessity for updated context-dependent performances and aspects related to the profession's vocational training become warranted. Most studies involve monomodal, bilingual subjects, with oral language proficiency (4,5) and consequently, the translation and interpretation of these oral and written languages (1,2) . Such studies are standard in research.…”
Section: Introductionmentioning
confidence: 99%